(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2012)
This article discusses the issue of word-formative modification of aspectual and phasal meanings of the Ukrainian verbs, which possess repetitive semantics. Systematic approach to the study of verbs, which possess multiplicative semantics, gives a possibility to identify semantic groups of verbs, determine specificity of aspectual and phasal modifications and means and conditions of its realization.